Air Susu Ibu Pondasi Kesehatan Optimal Bayi - Tomas, Chairul; Rarosa , Meta; Afrilia , Wiwin; Sari , Fikitri Marya (Jurnal Karya Nyata Pengabdian, 2025)
Exclusive breastfeeding during the first six months of a baby's life is very important to support optimal growth and development and increase the child's immune system. However, the success rate of exclusive breastfeeding is still relatively low in some regions. This study aims to determine the influence of health education on maternal knowledge about exclusive breastfeeding using a pre-post test design. The study was conducted on 15 pregnant women in the working area of the Periukan Water Health Center, precisely in the second hamlet of Sukasari Village. An intervention in the form of exclusive breastfeeding counseling was given once, and data was collected using questionnaires before and after the intervention. The results of the analysis showed a significant increase in mothers' knowledge after being educated, with an average pre-test score of 44 and post-test of 92. The results of the statistical test using the paired t-test showed a p value of < 0.05, which means that there was a significant difference before and after counseling. The conclusion of this study is that health education has a positive effect on increasing maternal knowledge about exclusive breastfeeding. It is recommended that educational activities like this be carried out on an ongoing basis to support exclusive breastfeeding practices in the community.